A Critical Review of the ASEAN Convention on the Protection of Women Migrant Workers: Gaps, Challenges, and Recommendations - Fitria, Naeli (CIC Lembaga Riset dan Konsultan Sosial, 2025)
This paper offers a critical examination of the ASEAN Convention on the Protection and Promotion of the Rights of Migrant Workers, with particular focus on the rights of women migrant workers. Employing constructivist international relations theory alongside feminist legal analysis, it identifies substantial shortcomings in implementation, normative ambiguity, and the limited enforceability of protections. Drawing on empirical data from 2020 to 2024, and informed by reports from international human rights and labor organizations, the paper provides a comprehensive assessment of ASEAN’s inadequacies in safeguarding women migrant workers. Women migrant workers continue to be disproportionately represented in domestic work and the informal economy, where they are subject to systemic discrimination, exploitation, and legal invisibility. Despite rhetorical commitments to gender equality and migrant rights, ASEAN’s legal frameworks and mechanisms frequently omit gender-specific provisions and lack the capacity to address intersectional vulnerabilities. The region’s reliance on soft law approaches and the absence of binding commitments undermine its ability to ensure effective protection. The paper concludes with strategic recommendations for ASEAN member states, including the adoption of legally binding commitments, the formulation of gender-sensitive regional instruments, the strengthening of accountability mechanisms, and more meaningful engagement with civil society organizations. Only through structural reform can ASEAN genuinely uphold the rights and dignity of women migrant workers.